2015
DOI: 10.1002/elps.201400309
|View full text |Cite
|
Sign up to set email alerts
|

Proteome profiling of keratinocytes transforming to malignancy

Abstract: To shed light on the multistep process of squamous cell carcinoma development and the underlying pathologic mechanisms, we performed comparative proteome analysis of keratinocytes, keratinocytes stimulated with Il-1beta, and A431 epidermoid carcinoma cells. Fractionation of the cells into supernatant, nucleus, and cytoplasm was followed by protein separation, proteolytic digest, and nano-LC separation, and fragmentation using an ion trap mass spectrometer. Specific bioinformatics tools were used to generate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Moreover, stimulation with IL-1 beta increased the level of proteins involved in nuclear factor kappa B (NF- κ B) communication pathway, in angiogenesis, and of those with antiapoptotic effect. Similar changes were found in epidermoid carcinoma cells suggesting an important role of inflammation in skin carcinogenesis [36]. …”
Section: Proteome Of Normal and Inflammatory Keratinocytessupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, stimulation with IL-1 beta increased the level of proteins involved in nuclear factor kappa B (NF- κ B) communication pathway, in angiogenesis, and of those with antiapoptotic effect. Similar changes were found in epidermoid carcinoma cells suggesting an important role of inflammation in skin carcinogenesis [36]. …”
Section: Proteome Of Normal and Inflammatory Keratinocytessupporting
confidence: 68%
“…A recent in vitro study [36] has identified 50 proteins considered specific to keratinocytes, most of them directly related to keratinocyte physiology. Some of these proteins, such as alpha-2 macroglobulin-like protein-1, alpha-2 macroglobulin-like protein 2, and interferon regulatory factor 6 (IRF-6) are involved in keratinocyte proliferation and differentiation.…”
Section: Proteome Of Normal and Inflammatory Keratinocytesmentioning
confidence: 99%
“…PathVisio software (23) was applied for specific analyses of defined pathways from Affymetrix arrays (Type Human Gene 1.0 ST Array). Proteomics analyses were conducted as described (24,25) .…”
Section: Methodsmentioning
confidence: 99%
“…UV exposure is considered as a complete carcinogen, since it affects each stage of carcinogenesis. In fact, it leads to cellular damage because of the reduction of cell-mediated immune responses, production of reactive oxygen species (ROS) and DNA alteration [ 5 , 6 , 7 , 8 ]. The earliest event after high UV exposure is keratinocyte apoptosis led by the p53/p21/bax/bcl-2 pathway followed by a hyperproliferative phase, leading to epidermal hyperplasia [ 5 , 6 ].…”
Section: Nmsc and Ak: Factors Involved In The Pathogenesismentioning
confidence: 99%